Analisis Islamic branding hotel syariah sebagai tujuan wisata halal - Ima, Asha Nur; Trishananto, Yudha (Nur Science Institute, 2022)
This study aims to examine the multisensory marketing and brand experience variables on brand loyalty by using the Muslim customer perceived value variable as an intervention. This study uses multiple linear regression and path analysis as research methods. The data used in this study is primary data, using survey questionnaires and interviews as data. The questionnaires distributed were 100 respondents. The object of this research is the Islamic hotel Multazam Kartasura. The results of this study indicate that the Multisensory Marketing variable has a positive and significant effect on Brand Loyalty. Then the Brand Experience and Moslem Customer Perceived Value variables have a positive and significant effect on Brand Loyalty. Multisensory Marketing and Brand Experience have a positive and significant effect on Muslim Customer Perceived Value. In the path analysis test, the Moslem Customer Perceived Value variable is able to mediate the influence of Multisensory Marketing and Brand Experience on Brand Loyalty.